2009
DOI: 10.1590/s0037-86822009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, toxicity and larvicidal and antifungal activities of Persea americana (avocado) seed extracts

Abstract: The present study had the aim of testing the hexane and methanol extracts of avocado seeds, in order to determine their toxicity towards Artemia salina, evaluate their larvicidal activity towards Aedes aegypti and investigate their in vitro antifungal potential against strains of Candida spp, Cryptococcus neoformans and Malassezia pachydermatis through the microdilution technique. In toxicity tests on Artemia salina, the hexane and methanol extracts from avocado seeds showed LC 50 values of 2.37 and 24.13mg mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
24

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 18 publications
2
73
0
24
Order By: Relevance
“…Although not specific, this method has a good correlation with tumor cells and pesticidal activity (Leite et al, 2009). This bioassay allows the evaluation of overall toxicity, and therefore it is considered the preliminary study of compounds with potential biological activity.…”
Section: Fructose Glucose and Sucrosementioning
confidence: 99%
See 1 more Smart Citation
“…Although not specific, this method has a good correlation with tumor cells and pesticidal activity (Leite et al, 2009). This bioassay allows the evaluation of overall toxicity, and therefore it is considered the preliminary study of compounds with potential biological activity.…”
Section: Fructose Glucose and Sucrosementioning
confidence: 99%
“…Nascimento et al (2008) studied toxicity in three species of medicinal plants of the genus Phyllanthus and reported absence of toxicity only in the species P.amarus. Leite et al (2009) found that hexane waste. Anthocyanin pigments are present in the grape skin, and their levels may vary from 30 to 750 mg/100g fruit, in agreement with the values found in this study (Bridle & Timberlake , 1997).…”
Section: Microbiological Qualitymentioning
confidence: 99%
“…One of the experiment 1 showed that avocado seeds were toxic to the method of Brine Shrimp Lethality Test/BST (LC 50 below 1000 ug/ml). Based on the results of previous studies 2,3 , LC 50 values obtained from the avocado seeds extract was less than 1000 mg/L. This value indicated that the avocado seeds were toxic.…”
Section: Introductionmentioning
confidence: 77%
“…Frações hexânica, etanóicae metanólica do óleo de abacate não demonstraram efeito antimicrobiano frente a cepas de C. albicans(ATCC 10231) 17 . No entanto, outros resultados publicados determinam atividade antimicrobiana das frações metanólica e hexânica do extrato da semente de abacate 23 . O efeito antifúngico do óleo essencial de C. cassiae C. winterianusfoi determinado em alguns estudos, em cepas bacterianas ou fúngicas 24,25 , no entanto existem diferenças em relação aos valores médios dos halos de inibição, quando da avaliação em meio sólido.Os valores encontrados no presente estudo são inferiores àqueles encontrados em estudo previamente realizado, o qual determina valores, médios de halos de inibição de 35 mm, entretanto frente a C. albicans 25 .…”
Section: Discussionunclassified